Penerapan Strategi Everyone Is Teacher Here Untuk Meningkatkan Pemahaman Siswa Pada Materi Bersatu Dalam Keragaman Dan Demokrasi Akan Bertambah Pada Mata Pelajaran Pendidikan Agama Islam di Kelas XII SMA Negeri 1 Siantan Tahun Pelajaran 2024/2025 - Abdul Hamid (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
This research aims to improve students' understanding of the material Unity in Diversity and Democracy Will Increase in Islamic Religious Education subjects using the Everyone Is Teacher Here strategy for class XII students at SMA Negeri 1 Siantan, Mempawah Regency. The form of this research is classroom action research (PTK), using a quantitative descriptive approach. The data collection technique uses direct observation using observation sheets and measurements using measurement tests and instruments for students' understanding of the material: Unity in Diversity and Democracy Will Increase. The subjects of this research were class XII students of SMA Negeri 1 Siantan, Mempawah Regency. After the data was collected and analyzed, the results of the analysis showed that using the Everyone Is Teacher Here strategy could increase students' understanding of the material: Unity in Diversity and Democracy Will Increase. In Pre-Cycle, the percentage of students who complete is 35%. After implementing the Everyone Is Teacher Here strategy in Cycle I, the percentage of students who completed it increased to 60%, and in Cycle II it increased again to 80%. So it can be concluded that the Everyone Is Teacher Here strategy in increasing students' understanding of the material Unity in Diversity and Democracy will increase in the Islamic Religious Education subject in class XII of SMA Negeri 1 Siantan, Mempawah Regency.